How Keynes came to Britain. (January 2016) - Skidelsky, Robert
Abstract : I explore how Keynesian ideas made their way into British public policy. I argue that the breakdown of pre-First World War macroeconomic conditions led to a 'blocked' system, where the adjustment mechanisms presupposed by classical economics were jammed, and that Keynesian economics offered an escape from this system. I explain the Keynesian response to the new problems in monetary and fiscal policy: the gold standard impeding credit control, and the tenacity of the balanced budget rule, respectively. Finally, I outline how Keynes's ideas took hold after the Great Depression via the events at the Macmillan Committee, and their policy implications.